Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Carryover Effects on Reproduction Can Buffer Against Mortality‐Driven Population Declines at Elevated Developmental Temperatures - Noah T. Leith; Anthony Macchiano; Brigitte Tenhumberg; Inaya Smith; Jake P. Woods; Kasey D. Fowler‐Finn (Ecology Letters, 2025)
Carryover effects broadly influence adult performance and population persistence. Although variation in developmental environments can have contrasting effects on survival and reproduction, current predictive models of vulnerability to environmental change typically ignore simultaneous changes in both fitness components. We tested how developmental temperatures shape survival and multiple aspects of reproduction in a plant‐living insect ( Enchenopa binotata treehoppers) and used population dynamic models to examine the cumulative impact of these complex effects on population growth. We show that elevated developmental temperatures increase adult fertility, offsetting reduced juvenile survival and potentially forestalling population declines following global warming. Moreover, pairing mates from different developmental temperatures exacerbated morphological mismatches between sexes, reducing mating success and sperm transfer. Our findings thereby provide novel evidence that thermal carryover effects can generate assortative mating and selection on adult reproductive morphology, in addition to shaping the relative importance of survival and reproduction for persistence in warming climates.

Caribbean Creep meets Chesapeake Creep: marine bioinvasions and community shifts along the Mid-Atlantic Coast, USA - Amy E. Fowler; April M. H. Blakeslee; Andrew Davinack; Robert Aguilar; Miranda Andersen; Clara Benadon; Henry H. C. Choong; Lindsay Green-Gavrielidis; Sarah R. Greenberg; El Hartshorn; Niels-Viggo Hobbs; Sara Labbe; et al. (Biological Invasions, 2025)
The Mid-Atlantic waters of North America are warming faster than > 90% of other global oceans, leading to significant increases in bottom water temperatures and influencing shifts in marine community structure. Given this modern-day scenario of significant community shifts over space and time, baseline surveys of species diversity are increasingly valuable. Therefore, we performed the first-ever marine bioinvasions Rapid Assessment Survey (RAS) along the Mid-Atlantic waters of the United States in June 2023, focused on marina floating pontoons in Virginia, Maryland, Delaware, and New Jersey. We recorded 29 non-indigenous, 16 cryptogenic, and 10 species that have expanded their ranges in the mid-Atlantic. Seven of these 10 species have expanded northwards from southern locations in the Caribbean (“Caribbean Creep”) or the western Atlantic (“Chesapeake Creep”), and three have expanded southwards. Five non-indigenous species (NIS) were found at more than 60% of the 10 sampled sites: the bryozoans Bugula neritina , Schizoporella pungens , Tricellaria inopinata, macroalgae Codium fragile subsp. fragile , and the sea anemone Aiptasiogeton eruptaurantia . We did not document any new nonindigenous species not already recorded on the Western Atlantic coast. All 10 communities were distinctly different, and species dominance varied by latitude and by site. This first-ever RAS of the Mid-Atlantic waters of the United States provides critical insight into how marine communities have been and are changing as a result of colonization by NIS, including those that have expanded their ranges as a result of human-induced climate change.

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

A Meta-Ethnography to Determine Critical Constructs of Nutrition Security - Caitlyn B. Faul; Stephanie Jilcott Pitts; Eric E. Calloway; Hilary K. Seligman; Heidi Reis; Cheryl Webb Cherry; Irene E. Hatsu; Oyinlola Toyin Babatunde; Alexandra L. MacMillan Uribe; Jared T. McGuirt; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

A multi-objective optimization model for cropland design considering profit, biodiversity, and ecosystem services - Caleb H. Geissler; Nathan L. Haan; Bruno Basso; Ames Fowler; Douglas A. Landis; Tyler J. Lark; Christos T. Maravelias (Ecological Modelling, 2025)

Integrating importance- performance analysis into transboundary natural resource management of water trails: Case study at the Chattahoochee river national recreation area water trail in Atlanta, GA (USA) - Benjamin T. Fowler; Gary T. Green; B. Bynum Boley (Journal of Outdoor Recreation and Tourism, 2024)

Passive biomonitoring for per- and polyfluoroalkyl substances using invasive clams, C. fluminea - Lauren A. Koban; Tabitha King; Thomas B. Huff; Kirin E. Furst; T. Reid Nelson; Andrew R. Pfluger; Mrudula Meghana Kuppa; Amy E. Fowler (Journal of Hazardous Materials, 2024)

Human‐modified habitats imperil ornamented dragonflies less than their non‐ornamented counterparts at local, regional, and continental scales - Michael P. Moore; Noah T. Leith; Kasey D. Fowler‐Finn; Kim A. Medley (Ecology Letters, 2024)
Biologists have long wondered how sexual ornamentation influences a species' risk of extinction. Because the evolution of condition‐dependent ornamentation can reduce intersexual conflict and accelerate the fixation of advantageous alleles, some theory predicts that ornamented taxa can be buffered against extinction in novel and/or stressful environments. Nevertheless, evidence from the wild remains limited. Here, we show that ornamented dragonflies are less vulnerable to extinction across multiple spatial scales. Population‐occupancy models across the Western United States reveal that ornamented species have become more common relative to non‐ornamented species over >100 years. Phylogenetic analyses indicate that ornamented species exhibit lower continent‐wide extinction risk than non‐ornamented species. Finally, spatial analyses of local dragonfly assemblages suggest that ornamented species possess advantages over non‐ornamented taxa at living in habitats that have been converted to farms and cities. Together, these findings suggest that ornamented taxa are buffered against contemporary extinction at local, regional, and continental scales.

Mineral–water reactions in Earth’s mantle: Predictions from Born theory and ab initio molecular dynamics - Sarah J. Fowler; David M. Sherman; John P. Brodholt; Oliver T. Lord (Geochimica et Cosmochimica Acta, 2024)

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Seasonal variation in the strength and consistency of tritrophic interactions among treehoppers, plants, and ants may favor generalist relationships - T. William Shoenberger; Kasey D. Fowler-Finn (Arthropod-Plant Interactions, 2024)

P16-30: Examining the need for an ovarian-specific steroidogenic assay to prioritize potential endocrine disrupting chemicals - P. Vazakidou; T. Li; L.L. Lecante; S. Mazaud-Guittot; P.A. Fowler; P. Damdimopoulou; P. Leonards; M. van Duursen (Toxicology Letters, 2023)

Multi-criteria analysis for rapid vulnerability assessment of marine species to climate change - Curtis Champion; James R. Lawson; Joanna Pardoe; Derrick O. Cruz; Ashley M. Fowler; Fabrice Jaine; Hayden T. Schilling; Melinda A. Coleman (Climatic Change, 2023)
The accelerating pace of climate-induced stress to global ecosystems threatens the sustainable management and conservation of biodiversity. To effectively respond, researchers and managers require rapid vulnerability assessment tools that can be readily implemented using diverse and existing knowledge sources. Here we demonstrate the application of multi-criteria analysis (MCA) for this purpose using a group of coastal-pelagic fishes from south-eastern Australia as a case-study. We show that MCA has the capacity to formally structure diverse knowledge sources, ranging from peer-reviewed information (which informed 29.2% of criteria among models) to expert knowledge (which informed 22.6% of criteria among models), to quantify the sensitivity of species to biophysical conditions. By integrating MCA models with spatial climate data over historical and future periods, we demonstrate the application of MCA for rapidly assessing the vulnerability of marine species to climate change. Spatial analyses revealed an apparent trend among case-study species towards increasing or stable vulnerability to projected climate change throughout the northern (i.e. equatorward) extent of the study domain and the emergence of climate refugia throughout southern (i.e. poleward) regions. Results from projections using the MCA method were consistent with past analyses of the redistribution of suitable habitat for coastal-pelagic fishes off eastern Australia under climate change. By demonstrating the value of MCA for rapidly assessing the vulnerability of marine species to climate change, we highlight the opportunity to develop user-friendly software infrastructures integrated with marine climate projection data to support the interdisciplinary application of this method.

Slab-failure or Slab-success? Examining the contributions of crust and mantle to post-subduction magmatism in the Ratagain Complex, NW Scotland - A. Lawrence; M. Fowler; C.G. Kingsbury; T. Knott; Darren Mark; C.T.E. Stevenson (Lithos, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Neural network classification of mobility spectra for volatile organic compounds using tandem differential mobility spectrometry with field induced fragmentation - P.E. Fowler; T. Bernat; J.Z. Pilgrim; G.A. Eiceman (Analytica Chimica Acta, 2023)

Conservation of endangered galaxiid fishes in the Falkland Islands requires urgent action on invasive brown trout - J. F. Minett; D. M. Fowler; J. A. H. Jones; P. Brickle; G. T. Crossin; S. Consuegra; C. Garcia de Leaniz (Biological Invasions, 2023)
Non-native salmonids are protected in the Southern hemisphere where they sustain aquaculture and lucrative sport fisheries, but also impact many native fishes, which poses a conservation conundrum. Legal protection and human-assisted secondary releases may have helped salmonids to spread, but this has seldom been tested. We reconstructed the introduction of brown trout ( Salmo trutta ) to the Falkland Islands using historical records and modelled its dispersal and probability of invasion using a generalized linear model and Leave One out Cross Validation. Our results indicate that establishment success was ~ 88%, and that dispersal was facilitated over land by proximity to invaded sites and density of stream-road crossings, suggesting it was human assisted. Brown trout have already invaded 54% of Falkland rivers, which are 2.9–4.5 times less likely to contain native galaxiids than uninvaded streams. Without strong containment we predict brown trout will invade nearly all suitable freshwater habitats in the Falklands within the next ~ 70 years, which might put native freshwater fishes at a high risk of extinction.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Evolutionary interactions between thermal ecology and sexual selection - Noah T. Leith; Kasey D. Fowler‐Finn; Michael P. Moore (Ecology Letters, 2022)
Thermal ecology and mate competition are both pervasive features of ecological adaptation. A surge of recent work has uncovered the diversity of ways in which temperature affects mating interactions and sexual selection. However, the potential for thermal biology and reproductive ecology to evolve together as organisms adapt to their thermal environment has been underappreciated. Here, we develop a series of hypotheses regarding (1) not only how thermal ecology affects mating system dynamics, but also how mating dynamics can generate selection on thermal traits; and (2) how the thermal consequences of mate competition favour the reciprocal co‐adaptation of thermal biology and sexual traits. We discuss our hypotheses in the context of both pre‐copulatory and post‐copulatory processes. We also call for future work integrating experimental and phylogenetic comparative approaches to understand evolutionary feedbacks between thermal ecology and sexual selection. Overall, studying reciprocal feedbacks between thermal ecology and sexual selection may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Accidental associates are not symbionts: the absence of a non-parasitic endosymbiotic community inside the common periwinkle Littorina littorea (Mollusca: Gastropoda) - James T. Carlton; April M. H. Blakeslee; Amy E. Fowler (Marine Biology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Primary central nervous system lymphoma in patients with and without HIV infection: a multicenter study and comparison with U.S national data - Dima Dandachi; Quinn T. Ostrom; Insun Chong; Jose A. Serpa; Thomas P. Giordano; Carol Kruchko; Jill S. Barnholtz-Sloan; Nathan Fowler; Rivka R. Colen; Fanny E. Morón (Cancer Causes & Control, 2019)

Age-Specific Patient Navigation Preferences Among Adolescents and Young Adults with Cancer - Samantha T. Pannier; Echo L. Warner; Brynn Fowler; Douglas Fair; Sara K. Salmon; Anne C. Kirchhoff (Journal of Cancer Education, 2019)

Contribution of large-scale midlatitude disturbances to hourly precipitation extremes in the United States - Renaud Barbero; John T. Abatzoglou; Hayley J. Fowler (Climate Dynamics, 2019)

Speed breeding for multiple disease resistance in barley - Lee T. Hickey; Silvia E. Germán; Silvia A. Pereyra; Juan E. Diaz; Laura A. Ziems; Ryan A. Fowler; Greg J. Platz; Jerome D. Franckowiak; Mark J. Dieters (Euphytica, 2017)

Pathogenic variation of Pyrenophora teres f. teres in Australia - R. A. Fowler; G. J. Platz; K. L. Bell; S. E. H. Fletcher; J. D. Franckowiak; L. T. Hickey (Australasian Plant Pathology, 2017)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

Mass Spectrometry-Based Quantification of CYP Enzymes to Establish In Vitro/In Vivo Scaling Factors for Intestinal and Hepatic Metabolism in Beagle Dog - Aki T. Heikkinen; Arno Friedlein; Jens Lamerz; Peter Jakob; Paul Cutler; Stephen Fowler; Tara Williamson; Roberto Tolando; Thierry Lave; Neil Parrott (Pharmaceutical Research, 2012)

A multi-model ensemble of downscaled spatial climate change scenarios for the Dommel catchment, Western Europe - Michelle T. H. van Vliet; Stephen Blenkinsop; Aidan Burton; Colin Harpham; Hans Peter Broers; Hayley J. Fowler (Climatic Change, 2012)

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Enterococcal prosthetic valve infective endocarditis: report of 45 episodes from the International Collaboration on Endocarditis-merged database - D. J. Anderson; L. Olaison; J. R. McDonald; J. M. Miro; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; E. Abrutyn; G. Habib; S. Eykyn; P. A. Pappas; V. G. Fowler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Coprecipitation of nonoxynol-9 with polyvinylpyrrolidone to decrease vaginal irritation potential while maintaining spermicidal potency - Philip T. Fowler; Gustavo F. Doncel; Paul M. Bummer; George A. Digenis (AAPS PharmSciTech, 2003)

Influence of hydrologic exchange patterns on water chemistry and hyporheic invertebrate communities in three gravel‐bed rivers - Reece T. Fowler; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2002)
The influence of hydraulic exchange patterns on hyporheic water chemistry and invertebrate community composition was measured in three gravel‐bed rivers of southern Hawke's Bay, North Island, New Zealand. Based on patterns reported overseas we predict that down‐welling waters will be similar to surface waters in chemical characteristics and epigean animals will be more common in down‐welling waters than in up‐wellings, which would have a different chemical signature to the surface waters and a fauna dominated by hypogean invertebrates. Conductivity, pH, and temperature of hyporheic water were least like those of surface waters at up‐wellings in the groundwater‐fed Makaretu River. Only 6% of the invertebrate fauna of these up‐wellings comprised epigean animals. In contrast, in the groundwater‐recharging Tukituki and Waipawa Rivers, hyporheic water chemistry was similar to that of surface water in down‐wellings and 40% of the community comprised epigean animals by abundance. Significant increases (P 0.05) in species diversity and taxonomic richness was also identified in down‐welling zones compared with up‐wellings. Species diversity and taxonomic richness were lowest in up‐wellings in the Makaretu where hypogean animals dominated the hyporheic fauna. Species diversity and taxonomic richness were higher in down‐wellings than up‐wellings because more epigean taxa were present.

Relative importance of surface and subsurface movement on benthic community recovery in the Makaretu River, North Island, New Zealand - Reece T. Fowler (New Zealand Journal of Marine and Freshwater Research, 2002)
Colonisation of macroinvertebrates following changes to the stream environment occurs rapidly through drift, oviposition, lateral movement, and vertical migration. To assess the influence of different sources of colonists on benthic macroinvertebrate community composition, a colonisation experiment using artificial substrate baskets was conducted in the braided Makaretu River in the southern Hawke's Bay (North Island, New Zealand). Both the numbers of taxa and individuals rapidly increased through time in baskets only allowing drifting and surface crawling invertebrates (surface), baskets only allowing invertebrates migrating from the hyporheic zone (hyporheic), and baskets that allowed both (controls). The numbers of taxa and density of individuals indicated that the artificial substrate baskets were similar to the benthos after 14 and 28 days, respectively. However, overall benthic community composition was not similar to the surrounding benthos until Day 42 in all three basket treatments. The colonisation rates identified from artificial baskets in the Makaretu River are consistent with other colonisation experiments undertaken in New Zealand and overseas. Elmidae (Coleoptera) was most abundant within surface treatments until Day 28 after which Deleatidium spp. (Ephemeroptera) became dominant. The abundance of Elmidae and Deleatidium in the control treatments was consistent with colonisation patterns in the surface baskets. Deleatidium dominated baskets allowing access from the hyporheic zone throughout the experiment. It appears that Elmidae colonise quickly in greater numbers by drifting and/or crawling and Deleatidium colonises more slowly from the hyporheic zone, eventually replacing Elmidae as the most common animal. This indicates that the hyporheic zone provides a source of invertebrate colonists later during community recovery, whereas drifting and/or crawling provides colonists early during recovery.

The effect of environmental stability on hyporheic community structure - R. T. Fowler; R. G. Death (Hydrobiologia, 2001)

Effects of channel morphology on temporal variation in invertebrate community structure in two North Island, New Zealand rivers - R. T. Fowler; R. G. Death (New Zealand Journal of Marine and Freshwater Research, 2000)
Abundance and species composition of benthic invertebrate communities were investigated in two rivers of contrasting channel form, the Tukipo and Waipawa, in the Southern Hawke's Bay, New Zealand. Monthly collections between December 1995 and December 1996 yielded a total of 89 taxa from the two sites; Deleatidium spp. numerically dominating the braided Waipawa whereas Pycnocentrodes spp., Pycnocentria funerea, Aoteapsyche spp., and Elmidae were most common in the constrained Tukipo. Although disturbance frequency was similar between rivers, the streambed substrates were smaller, and hence less stable in the Waipawa. Number of taxa, total abundance, and community composition changed through time in both rivers. The Waipawa community changed least throughout the year; perhaps because of greater numbers of rare taxa at the Tukipo whereas greater resilience of taxa and community dominance by the mobile generalist Deleatidium spp. in the Waipawa lead to greater constancy. At a broader taxonomic scale, invertebrate communities of the Waipawa were also more similar to communities in two South Island braided rivers (Ashley and Rakaia) than the Tukipo. Thus, although braided river communities may show some similarities throughout New Zealand, the community of the constrained channel was clearly different both in taxonomic composition and temporal change of that composition.

CHARACTERIZATION OF JOK-1, A HUMAN GASTRIC EPITHELIAL CELL LINE - N. OKAYAMA; M. R. FOWLER; S. R. JENNINGS; P. PATEL; R. SPECIAN; B. ALEXANDER; T. H. JACKSON; T. OSHIMA; K. SHANNON; J. S. ALEXANDER (In Vitro Cellular & Developmental Biology - Animal, 2000)

Organochlorine pesticides and polychlorinated biphenyls in the Arctic Ocean food web - B. T. Hargrave; G. C. Harding; W. P. Vass; P. E. Erickson; B. R. Fowler; V. Scott (Archives of Environmental Contamination and Toxicology, 1992)